THE IMPLEMENTATION OF NIKAH SIRI WITH THE PURPOSE OF MAINTAINING FAMILY SALARY BENEFITS: THE PERSPECTIVE OF ISLAMIC LAW - Ramlah Ramlah Ramlah (INNOVATIO: Journal for Religious Innovations Studies, 2022)
This paper aims to determine the implementation of “Nikah Siri” (Unofficially, unregister marriages) with the aim of maintaining family salaries. “Nikah Siri” namely marriages carried out under the hands, not officially registered in front of the Office of Religious Affairs (it is called KUA in Indonesia), or they are not published because they are secret, but they are carried out in accordance with Islamic law. There are two opinions of Nikah Siri in terms of the perspective of Islamic law, namely ‘allowed’ or ‘prohibited’. It is permissible if the marriage under the hand (siri) is carried out in accordance with the terms and pillars of Islamic marriage. It is prohibited when it is invalid because it does not describe legal certainty for future generations and violates the rules contained in Law no. 1 of 1974. This law is the consensus of the Ulama' that Muslims must obey to ensure legal certainty and the benefit of the ummah. The implementation of Nikah Siri with the purpose of maintaining family salaries, including fraud against the state, which should be a husband who receives a pension from his deceased wife if he remarries another woman, the pension salary is stopped according to Indonesian laws and regulations. Abstrak: Tulisan ini bertujuan untuk mengetahui pelaksanaan nikah siri dengan tujuan mempertahankan gaji keluarga. Nikah Siri yakni nikah yang dilaksanakan dan tidak didaftarkan secara resmi di depan Petugas Pencatat Nikah (KUA), tidak dipublikasikan kerena sifatnya secara diam-diam, tapi dilaksanakan sesuai dengan hukum Islam. Nikah Siri ditinjau dari perspektif Hukum Islam, terdapat dua pendapat yakni boleh atau dilarang. Pendapat yang menyatakan boleh, bila nikah siri dilaksanakan sesuai dengan syarat dan rukun perkawinan Islam. Pendapat yang melarang nikah siri tidak sah karena tidak menggambarkan kepastian hukum bagi generasi penerusnya dan menyalahi aturan yang terkandung dalam UU No. 1 Tahun 1974, dimana undang-undang ini merupakan ijma’ para Ulama’ yang wajib ditaati umat Islam untuk menjamin kepastian hukum dan kemashlahatan ummat. Nikah siri yang pelaksanaannya dibarengi dengan motivasi untuk mempetahan gaji keluarga, termasuk kepada penipuan terhadap negara, yang seharusnya suami yang mendapat pensiunan dari almarhumah isterinya bila menikah lagi dengan perempuan lain, maka gaji pensiun tersebut terhenti menurut peraturan perundang-undangan Indonesia. Keyword: nikah siri, tunjangan keluarga, dan hukum Islam